2000
DOI: 10.1191/135245800678827806
|View full text |Cite
|
Sign up to set email alerts
|

Sustained clinical benefits of glatiramer acetate in relapsing multiple sclerosis patients observed for 6 years

Abstract: In a randomized, placebo-controlled, double-blind study, glatiramer acetate (Copaxone) reduced the relapse rate and slowed accumulation of disability for patients with relapsing - remitting multiple sclerosis. Of the original 251 patients randomized to receive glatiramer acetate or placebo, 208 chose to continue in an open-label study with all patients receiving active drug. The majority of the original double-blind cohort continues to receive glatiramer acetate by daily subcutaneous injection and are evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0
2

Year Published

2002
2002
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 10 publications
6
99
0
2
Order By: Relevance
“…In MS therapy, several clinical trials have demonstrated the efficacy of glatiramer acetate (GA; copolymer-1; Copaxone ® ) in reducing the relapse rate and the magnetic resonance imaging (MRI)-defined disease activity in patients with a relapsing-remitting (RR) course [5, 6, 7]. Current concepts propose that GA, initially developed to mimic a major component of the myelin sheath, myelin basic protein, leads to partial activation and tolerance induction of myelin-specific T cells, and/or an induction of GA-reactive T helper 2 (Th2)-type regulatory cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…In MS therapy, several clinical trials have demonstrated the efficacy of glatiramer acetate (GA; copolymer-1; Copaxone ® ) in reducing the relapse rate and the magnetic resonance imaging (MRI)-defined disease activity in patients with a relapsing-remitting (RR) course [5, 6, 7]. Current concepts propose that GA, initially developed to mimic a major component of the myelin sheath, myelin basic protein, leads to partial activation and tolerance induction of myelin-specific T cells, and/or an induction of GA-reactive T helper 2 (Th2)-type regulatory cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cop1 was originally designed to induce EAE, but instead was found to be effective in suppressing EAE (20)(21)(22)(23) and is in current use in the treatment of relapsing-remitting forms of MS (24)(25)(26). A recent clinical study demonstrated its sustained efficacy in MS patients over a period of 6 years (27). Nevertheless, Cop1 only has a modest effect on the course of the disease.…”
mentioning
confidence: 99%
“…1. There are hints from the six years observation period of the Copaxone study in the U. S. indicating that starting treatment at an earlier time may be associated with a reduced risk for disease progression as measured by the EDSS [23]. Similar results were also extracted from data derived from the pivotal studies with interferon-beta preparations in RRMS.…”
Section: ■ Early Therapy With Other Immuno-modulatory Substancesmentioning
confidence: 81%
“…Open label, follow-up examinations revealed a continuous treatment effect if compared to the natural disease course [23]. The 9-month results of a placebocontrolled study on the influence of Copaxone® on the subclinical disease activity as measured by cranial MRI were recently published [8].…”
Section: ■ Glatiramer Acetate In Relapsing Msmentioning
confidence: 98%